Eksistensi home industry berbasis gender di Kota Malang - Anggaunitakiranantika Anggaunitakiranantika (Universitas Negeri Malang, 2019)
There are many industry sector in Malang City, one of them is Cornflakes Industry which located on Kelurahan Pandanwangi, Kecamatan Blimbing, Malang City. This industry, is running for over 25 years and must facing business competition in industrialized era. For their sustainability, this industry is supported by social capital strengthness. In order to preserving home industries which producing cornflake, there are some components in society who directly supports such as: business owner, employee, and laborer. Research was conducted by qualitative research with gender approach. This research aims for analyzing social capital role on cornflake home industry in Malang City, elaborating social phenomena in industrial sector with economy sociological context and identifying how social capital works on cornflake industrial relationship in Malang City. Research was found that social capital among industrial relation are created social bonding among societies which created by kinship and neighborhood system, then, strengthening cooperation between employee, employer, labor, supplier, consumen and Malang City government for supporting each other due to local commodity from home industry sector. Finally, research finding if social capital will determined industrial existences in the future based on product necessity like cornflake as local commodity has declared by Tourism Indonesia Government as premium local food product from Malang City.DOI: 10.17977/um022v4i12019p038